Check the Balance: Is the Doctrine of Separation of Powers Sufficient in the Context of Intergovernmental Organisations? A Case Study of Australia's AML/CTF Financing Framework. (December 2022) - Goldbarsht, Doron; Harris, Hannah
This article demonstrates the pressing need to rethink the doctrine of separation of powers in Australia in light of the increasing influence of intergovernmental organisations such as the Financial Action Task Force ('FATF'), which are shaping domestic lawmaking. The article documents the influence of the FATF on Australia's anti-money laundering and counter-terrorism financing framework, showing how FATF 'recommendations' are in fact decrees that Australia and other nation states integrate into their domestic legal systems — even when the legislative branch of government does not support such actions. The article suggests that Australia should consider implementing a fourth arm of government — an integrity arm — to strengthen the nation against the influence of intergovernmental organisations.